Flame Retardant Hybrid Paper Coatings with PVA - Melamine / Zinc Borat - Arman Kandirmaz, Emine (Journal of Graphic Engineering and Design, 2020)
Papers are raw materials with high flammability. Some of the products produced in the printing industry are used in places requiring high heat resistance. High-tech papers can be produced by adding a flame retardant to the paper coating formulation or pulp. In this study, it is aimed to prepare polyvinyl alcohol (PVA )- zinc borate / melamine / zinc borate-melamine paper coating formulations and to produce flame retardant paper by coating on paper. For this purpose, primarily zinc borate is produced by boric acid and zinc carbonate reaction . In the second part of the study, four different coating formulations were prepared by adding zinc borate, melamine and their double mixtures to the main formulation, where PVA polymer matrix was used as binder, and coatings were made on an 80g/m2 paper surface. Limiting oxygen index (LOI ), gloss, color, surface energy and contact angles properties of the produced papers were determined. Offset printing was done onto coated papers with IGT C1 test printing machine. All produced flame retardant papers have good printability characteristics.